2011
DOI: 10.1016/j.tvjl.2011.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Expanded dog leukocyte antigen (DLA) single nucleotide polymorphism (SNP) genotyping reveals spurious class II associations

Abstract: The dog leukocyte antigen (DLA) system contains many of the functional genes of the immune system, thereby making it a candidate region for involvement in immune-mediated disorders. A number of studies have identified associations between specific DLA class II haplotypes and canine immune hemolytic anemia, thyroiditis, immune polyarthritis, type I diabetes mellitus, hypoadrenocorticism, systemic lupus erythematosus-related disease complex, necrotizing meningoencephalitis (NME) and anal furunculosis. These stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 72 publications
1
25
0
Order By: Relevance
“…In Safra’s review of clinical disease in 53 affected Weimaraners, ~ 50% of the dogs had at least one affected littermate (36). Linkage to the DLA-DRB1*01501 (DLA is the dog equivalent of the HLA) was reported by Abeles et al (38) but no association could be found with the DLA locus when expanded DLA SNP analysis was performed (39) nor in another study assessing the role of DLA-DQA1 locus(40). The search for the disease causing gene is ongoing using a next generation sequencing approach.…”
Section: Canine Hypertrophic Osteodystrophymentioning
confidence: 96%
“…In Safra’s review of clinical disease in 53 affected Weimaraners, ~ 50% of the dogs had at least one affected littermate (36). Linkage to the DLA-DRB1*01501 (DLA is the dog equivalent of the HLA) was reported by Abeles et al (38) but no association could be found with the DLA locus when expanded DLA SNP analysis was performed (39) nor in another study assessing the role of DLA-DQA1 locus(40). The search for the disease causing gene is ongoing using a next generation sequencing approach.…”
Section: Canine Hypertrophic Osteodystrophymentioning
confidence: 96%
“…34À36 Largebreed dogs, particularly Weimeraners, develop a disease that is phenotypically similar to human CRMO called hypertrophic osteodystrophy (HOD). 37,38 This disease clusters in litters and in specific breeds, strongly supporting a genetic component. 38 There are also two autosomal recessive human disorders that have CRMO as a subphenotype, including Majeed syndrome, which is due to mutations in LPIN2, and deficiency of the interleukin-1 receptor antagonist (DIRA), which is due to mutations in IL1RN.…”
Section: Geneticsmentioning
confidence: 87%
“…37,38 This disease clusters in litters and in specific breeds, strongly supporting a genetic component. 38 There are also two autosomal recessive human disorders that have CRMO as a subphenotype, including Majeed syndrome, which is due to mutations in LPIN2, and deficiency of the interleukin-1 receptor antagonist (DIRA), which is due to mutations in IL1RN. 39À41 Pathogenesis Innate immune system dysfunction is responsible for the chronic bone and skin inflammation seen in these disorders.…”
Section: Geneticsmentioning
confidence: 87%
“…The canine MHC (dog leucocyte antigen, DLA) has been associated with hypoadrenocorticism (Massey and others 2013) although this was based on DRB1/DQA1/DQB1 exon 2 typing and could be subjected to population stratification as reported by Safra and others for Nova Scotia duck tolling retrievers with hypoadrenocorticism and Weimaraners with hypertrophic osteodystrophy (Safra and others 2011). There is, however, a reported genetic basis in a number of breeds (Shaker and others 1988, Burton and others 1997, Oberbauer and others 2002, 2006, Famula and others 2003, Chase and others 2006, Hughes and others 2007, 2009, Short and others 2013) with anecdotal reports in others (West Highland white terrier, great dane and soft coated wheaten terrier).…”
mentioning
confidence: 99%
“…This dog population may also exhibit clinical heterogeneity between breeds but it is likely that the cause of hypoadrenocorticism within a breed is the same; further DLA analysis, in particular, extended DLA analysis (Safra and others 2011) should enable us to identify breeds that have a strong autoimmune component.…”
mentioning
confidence: 99%